Relationship-based Intervention with Young Children with Autism in Saudi Arabia: Impediments and Consequences of Parenting Stress and Depression. Issue 3 (4th May 2019) - Alquraini, Turki; Al-Odaib, Ali; Al-Dhalaan, Hesham; Merza, Haniah; Mahoney, Gerald
ABSTRACT: This investigation examined the consequences and effects of the severity of mothers psychosocial functioning as assessed by measures parenting stress and depression in a randomised control trial of a Relationship-based Intervention (RBI) called Responsive Teaching (RT). The sample included 28 parents and preschool aged children with Autism from Saudi Arabia. RT subjects received weekly parent–child intervention sessions for 4 months. Dependent variables were mothers' style of interaction as assessed by the PICCOLO at post intervention as well as pre- and post-measures of parenting stress and depression. There were three findings from this study. First, mothers who participated in this study had extremely high levels of psychosocial dysfunction. Nearly all reported clinical levels of parenting stress and more than 40% reported clinical levels of depressive symptoms. Second, high levels of psychosocial dysfunction did not prevent mothers from participating in RT as indicated by their ability to integrate RT strategies into their interactions with their children. Third, RT was associated with substantial improvements in mother's parenting stress and depression. Implication for early intervention practice are discussed.